An effortless hybrid method to solve economic load dispatch problem in power systems - Pourakbari-Kasmaei, M.; Rashidi-Nejad, M. (Energy conversion and management, 2011)
► We proposed a fast method to get feasible solution and avoid futile search. ► The method dramatically improves search efficiency and solution quality. ► Applied to solve constrained ED problems of power systems with 6 and 15 unit. ► Superiority of this method in both aspects of financial and CPU time is remarkable. This paper proposes a new approach and coding scheme for solving economic dispatch problems (ED) in power systems through an effortless hybrid method (EHM). This novel coding scheme can effectively prevent futile searching and also prevents obtaining infeasible solutions through the application of stochastic search methods, consequently dramatically improves search efficiency and solution quality. The dominant constraint of an economic dispatch problem is power balance. The operational constraints, such as generation limitations, ramp rate limits, prohibited operating zones (POZ), network loss are considered for practical operation. Firstly, in the EHM procedure, the output of generator is obtained with a lambda iteration method and without considering POZ and later in a genetic based algorithm this constraint is satisfied. To demonstrate its efficiency, feasibility and fastness, the EHM algorithm was applied to solve constrained ED problems of power systems with 6 and 15 units. The simulation results obtained from the EHM were compared to those achieved from previous literature in terms of solution quality and computational efficiency. Results reveal that the superiority of this method in both aspects of financial and CPU time.